In vitro activity of ethanolic and water extract of guava leaves at various concentrations against Lactobacillus acidophilus - Deepika Jain; Pralhad Dasar; Sandesh Nagarajappa; Sandeep Kumar; Bhuvnesh Airen; Shilpa Warhekar (Wolters Kluwer Medknow Publications, 2014)
Introduction: Chemical substances used for prevention of dental caries are known to have many side-effects. Thus, natural products should be explored for their anticaries action. Objectives: To prepare 5% and 20% concentrations of ethanolic and water extracts of guava leaves and to assess their activity against Lactobacillus acidophilus. Materials and Methods: In vitro experimental study was conducted in Department of Biosciences. Ethanolic and water extracts of guava leaves were prepared using Soxhlet extractor. Two concentrations 5% and 20% weight/volume of both extracts were prepared. Test organism L. acidophilus Microbial Type Culture Collection 447 was obtained in lyophillized form. After revival in nutrient broth, bacteria were grown on Lactobacilli de Man, Rogosa, Sharpe agar for further experiment. Antimicrobial testing of extracts was done using Agar well-diffusion method. Ten plates each were prepared for both extracts. Chlorhexidine (0.2%) served as a positive control and distilled water as a negative control. Results: Mean zone of inhibition produced by 5% and 20% ethanolic extract was 11.2 mm and 14.1 mm respectively and by 5% and 20% water extract was 1.6 mm and 5.1 mm respectively. Statistical analysis of results using one-way ANOVA and post-hoc Tukey's test revealed that activity of 5% ethanolic extract and 5%, 20% water extract was significantly less than that of 0.2% chlorhexidine. There was no statistical difference in efficacy of 20% ethanolic extract of guava and 0.2% chlorhexidine (P = 0.270). Conclusion: Ethanolic and water extracts of guava leaves possess antibacterial activity against L. acidophilus with 20% ethanolic extract being as efficacious as 0.2% chlorhexidine.